The nongovernmental sector in disaster resilience : conference recommendations for a policy agenda - Acosta, Joie D.; Chandra, Anita; Sleeper, Sally; Springgate, Benjamin F.; Rand eBooks (Santa Monica, CA : RAND, 2011)
Nongovernmental organizations (NGOs) are instrumental in communities$1 (Bresilience to natural and man-made disasters. But, despite national progress, the plans and processes for their involvement are not well-defined. This report summarizes three interrelated conference sessions that RAND researchers convened during the Louisiana Association of Nonprofit Organizations annual conference in August 2010. The purpose of the three sessions was to generate a national policy agenda that summarizes the challenges to involving NGOs in disaster response and recovery and to identify potential policy and program recommendations to address these challenges, with a specific emphasis on two types of populations, which were most in need after recent disasters: displaced and returning individuals and individuals with mental health needs. Panelists and conference attendees were asked to identify recommendations that would assist NGO involvement in disaster response and recovery. Those recommendations were then summarized by RAND researchers and were categorized into five areas: defining and formalizing roles for NGOs, structure and integration of governmental and nongovernmental organizations in common plans, information sharing, service capacity, and resource allocation. Based on the conference discussion, this report also contains RAND recommendations for future research to inform implementation of the policy agenda.s
Introduction -- A national policy agenda to improve nongovernmental organizations' involvement in disaster response and recovery -- Session 1 summary : the role of NGOs in disaster response and recovery -- Session 2 summary : the role of NGOs in supporting displaced and returned populations -- Session 3 summary : the role of NGOs in postdisaster mental health services and psychological recovery -- Future research opportunities -- Next steps and conclusions -- Appendix: Expert panel members, by session.
"This work was carried out in collaboration with the RAND Gulf States Policy Institute, and within the divisions of RAND Infrastructure, Safety, and Environment and RAND Health"--Preface.
"RAND Gulf States Policy Institute."
Includes bibliographical references (p. 37-40).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Disaster relief; Non-governmental organizations; Disaster Planning -- organization & administration; Health Services Needs and Demand; Mental Health; Private Sector -- organization & administration; Electronic books